1998
DOI: 10.1182/blood.v92.5.1639.417k10_1639_1645
|View full text |Cite
|
Sign up to set email alerts
|

Severe Factor VII Deficiency Due to a Mutation Disrupting an Sp1 Binding Site in the Factor VII Promoter

Abstract: We have identified a point mutation in the promoter of the factor VII gene responsible for a severe bleeding disorder in a patient from a large French-Canadian family with known consanguinity. The proband has an extremely low plasma level of factor VII antigen and factor VII coagulant activity (<1 percent of normal) and suffers from hemarthroses and chronic arthropathy. Sequencing of the patient’s factor VII 5′ flanking region, intron/exon junctions, and coding regions showed a homozygous point mutation, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 43 publications
5
28
0
Order By: Relevance
“…While the incidence of FVII deficiency in the general population is approximately one in 500 000, in the French‐Canadian population of the small village where it was studied, the incidence is approximately one in 335 [11]. A mutation of a C to G transversion at position −94 within the core binding site of transcription factor Sp1 was identified as the mutation most commonly responsible for FVII deficiency in this population [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the incidence of FVII deficiency in the general population is approximately one in 500 000, in the French‐Canadian population of the small village where it was studied, the incidence is approximately one in 335 [11]. A mutation of a C to G transversion at position −94 within the core binding site of transcription factor Sp1 was identified as the mutation most commonly responsible for FVII deficiency in this population [12].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) In vitro replacement of recombinant factor VIIa : Three CRM– FVII‐deficient individuals (subjects 1–3) were selected from the French‐Canadian descendent pool of FVII‐deficient individuals [11,12]. Sequencing the subjects FVII promoter region, confirmed that these individuals were homozygous for the −94 C to G transversion.…”
mentioning
confidence: 99%
“…The found new DNA polymorphisms in the promoter region (Ϫ122T>C) and in intron 1a (73G>A) were detected by sequencing or restriction analysis by BmyI and MspI, respectively. 6,7…”
Section: Methodsmentioning
confidence: 99%
“…2,4,5 FVII activity is influenced not only by mutations of the factor VII gene but also by allelic polymorphic variations of the gene. Eight polymorphisms within FVII gene are known, 6,7 three of which influence the level of FVII activities: an insertion polymorphism of the promotor, 8 a repeat polymorphism within intron 7, [9][10][11][12] and the Arg353 Gln polymorphism of exon 8. 13 The hemorrhagic diathesis in patients with FVII deficiency can be highly variable and does not necessarily correlate with the level of FVII activities.…”
Section: Abstract: Fvii Deficiency Fvii Gene Mutations Haplotype Anmentioning
confidence: 99%
“…Low mRNA expression ELISA/CA/qRT-PCR [73] SPCD Arg277Cys LP Low secretion/ moderate activity ELISA/CA/qRT-PCR [73] SPCD Arg353Gln Benign None ELISA/CA/qRT-PCR [73] Gla domain Ser23Pro PA LTB Crystallography/CA [54] EGF-like-2 domain Cys135Arg PA Disrupted disulfide bond Crystallography/CA [54,74] SPCD Arg247Cys PA LTB Crystallography/CA [54] SPCD Ser282Arg PA LTB Crystallography/CA [54] SPCD Ser363Ile PA LTB Crystallography/CA [54] SPCD Trp364Cys PA LTB Crystallography/CA [54] SPCD Trp364Phe PA LTB Crystallography/CA [54] SPCD Pro303Thr PA LTB Crystallography/CA/ELISA/ solid-phase binding assay [54,60] Gla domain Phe24del PA LTB Crystallography/CA [56] EGF-like-2 domain Arg110Cys PA IPF Clotting assay/EIA [18] EGF-like-2 domain Asp123Tyr PA IPF Clotting assay/EIA [18] Promoter -94C>G PA Low Sp1 binding Reporter gene expression assay/ electrophoretic mobility shift assay [75] SPCD, serine protease catalytic domain; PA, pathogenic; LP, likely pathogenic; LS, low secretion; LCA, low coagulative activity; LTB, low TF binding; IPF, impaired protein folding; HE, high expression; LE, low expression; CM, confocal microscopy; FM, fluorescence microscopy; CA, coagulation assay; Ref. reference of FVIIa is not well known, previous studies have indicated that different F7 gene variations can change this interaction and decrease the coagulation activity of the protein [54] .…”
Section: Spcd G420vmentioning
confidence: 99%